2016
DOI: 10.1186/s40064-016-2730-3
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure analysis and forensic evaluation of Xinjiang Uigur ethnic group on genomic deletion and insertion polymorphisms

Abstract: BackgroundThe Uigur ethnic minority is the largest ethnic group in the Xinjiang Uygur Autonomous Region of China, and valuable resource for the study of ethnogeny. The objective of this study was to estimate the genetic diversities and forensic parameters of 30 insertion-deletion loci in Uigur ethnic group from Xinjiang Uigur Autonomous Region of China and to analyze the genetic relationships between Xinjiang Uigur group and other previously published groups based on population data of these loci.ResultsAll th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…For Uygur, Han and Mongolian populations, previous research investigated their genetic variations based on different genetic markers (Mei et al, 2016; Tao et al, 2018). Tao et al (2018) assessed genetic polymorphisms of 12X-STRs and found that the Mongolian group showed indistinguishable genetic component distributions when compared to the components of Han populations in different regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Uygur, Han and Mongolian populations, previous research investigated their genetic variations based on different genetic markers (Mei et al, 2016; Tao et al, 2018). Tao et al (2018) assessed genetic polymorphisms of 12X-STRs and found that the Mongolian group showed indistinguishable genetic component distributions when compared to the components of Han populations in different regions.…”
Section: Discussionmentioning
confidence: 99%
“…Tao et al (2018) assessed genetic polymorphisms of 12X-STRs and found that the Mongolian group showed indistinguishable genetic component distributions when compared to the components of Han populations in different regions. Mei et al (2016) conducted genetic differentiation analyses between Uygur and other reference populations based on 30 InDels and found that Uygur group was far from Han populations and other Chinese populations in the PCA plot. In this study, we selected 48 SNPs to differentiate Han, Mongolian and Uygur populations.…”
Section: Discussionmentioning
confidence: 99%
“…Uighur is the major ethnic group there, accounting for 45.2% of the population compared with 40.6% with Han ethnicity . The Uighur population numbered 10.06 million in 2010 . They mainly live in Kashi, located in the south of Tianshan Mountain, and others are scattered in the Ili and Urumchi areas.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…They mainly live in Kashi, located in the south of Tianshan Mountain, and others are scattered in the Ili and Urumchi areas. The Uighurs have their own language and their Islamic beliefs have a great influence on their culture and customs …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The commercially available Investigator DIPplex kit which contains 30 autosomal InDel loci and an amelogenin gene has been testified in a large majority of populations to evaluate its efficiency for forensic applications. Chinese population data including Tujia ( Shen et al, 2016 ), Uyghur ( Mei et al, 2016 ), Xibe ( Meng et al, 2015 ), Hui ( Xie et al, 2018 ), Dong ( Li et al, 2015 ), Tibetan ( Guo et al, 2016 ), Kazak ( Kong et al, 2017 ), Zhuang ( Li et al, 2015 ), and Yi ( Li et al, 2015 ) were reported previously. But data in existence did not incorporate Dongxiang ethnic minority in Gansu province of China.…”
Section: Introductionmentioning
confidence: 98%